(untitled) (Itinera, 2021)
The sublime is a concept that has never ceased to attract and to fascinate scholars. In its classical formulation, it dates back to the eighteenth century, but some of the issues that characterize its origin – such as the border between representation and the unrepresentable, or between form and formless, pleasure and terror – return strongly in contemporary thinking. In this regard, opinions are divided. Is the sublime an already outdated notion that can only be discussed from a historical point of view? Or does it also contain important elements for the current philosophical debate? Moreover, have the transformations that the sublime has undergone in the contemporary world substantially distorted it, or have they instead brought to light some new possible implications of this concept? This issue of "Itinera" is dedicated to these and other similar questions, starting from the traditional definitions of the sublime between the eighteenth and nineteenth centuries, until its most recent interpretations.